Cardiovascular and respiratory effects of the degree of head‐down angle during robot‐assisted laparoscopic radical prostatectomy. Issue 1 (25th January 2013) - Kadono, Yoshifumi; Yaegashi, Hiroshi; Machioka, Kazuaki; Ueno, Satoru; Miwa, Sotaro; Maeda, Yuji; Miyagi, Tohru; Mizokami, Atsushi; Fujii, Yuka; Tsubokawa, Tsunehisa; Yamamoto, Ken; Namiki, Mikio
Abstract Background Robot‐assisted laparoscopic radical prostatectomy (RALP) requires a steep Trendelenburg position and CO2 pneumoperitoneum for several hours to secure the surgical visual field. The present study was performed to investigate the influence of each angle of Trendelenburg position during RALP on cardiovascular and respiratory homeostasis. Methods Forty‐seven ASA physical status 1 and 2 patients underwent open retropubic radical prostatectomy (RRP) or RALP. Patients receiving RALP were randomized to undergo the operation in the 20°, 25° or 30° Trendelenburg position. Heart rate (HR), mean arterial pressure (MAP), respiratory rate (RR), end‐tidal CO2 pressure (PetCO2), tidal volume (Vt), peak inspiratory pressure (PIP) and dynamic compliance (Cdyn) were recorded during the operation. Results Angle of head‐down tilt was significantly correlated with MAP, PIP and Cdyn, but not with HR, RR or PetCO2. MAP decreased gradually over time in each group in the Trendelenburg position with pneumoperitoneum. As the angle of head‐down tilt became stronger, MAP, RR, PetCO2 and PIP tended to increase and Cdyn tended to decrease. Conclusions This study demonstrated that the degree of the head‐down angle at RALP affected the cardiovascular and respiratory parameters. Pneumoperitoneum with head‐down position in RALP influenced the cardiovascular and respiratory system to a greater extent than RRP, and these effects were stronger with deeper head‐down angle. Copyright © 2013 John Wiley & Sons, Ltd.